1982
DOI: 10.1149/1.2123968
|View full text |Cite
|
Sign up to set email alerts
|

An Ellipsometric Study of Electrochromism in Tungsten Oxide

Abstract: A self‐nulling ellipsometer was used to follow the optical changes which occur when galvanostatic anodic oxidation of tungsten in 0.5M sulfuric acid is interrupted at 5V intervals by the application of cathodic transients which color the oxide film. The film undergoes two distinct optical changes during the cathodic cycle, the first due to the strain and anisotropy resulting from electrostriction, and the second due to the optical absorption associated with electrochromism. For color cycles of limited duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The results in the previous section show that hydrogen does not build up uniformly in tungsten oxide, as was previously reported (2,3). It forms a distinct phase, HWO3, and reduction and reoxidation proceed in the same way as in the molybdenum (4, 5) and vanadium (6, 7) systems, by motion of a phase boundary across the film.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The results in the previous section show that hydrogen does not build up uniformly in tungsten oxide, as was previously reported (2,3). It forms a distinct phase, HWO3, and reduction and reoxidation proceed in the same way as in the molybdenum (4, 5) and vanadium (6, 7) systems, by motion of a phase boundary across the film.…”
Section: Discussionsupporting
confidence: 77%
“…The first paper in this series (1) dealt with optical anisotropy in the oxide, and its findings are used in the optical analysis in the current study. Most of our earlier work (2,3) on the optical effect of electrochemical processes (electrochromism) in tungsten oxide was done in sulfuric acid electrolyte, but some work was done in acetic acid, and we found that the oxide could be made more absorbing optically in the nonaqueous electrolyte. We found that the optical data exhibited little hysteresis when the oxide was reduced (colored) and then reoxidized (bleached), and we fit the data to a model in which optical changes take place uniformly throughout the film.…”
mentioning
confidence: 80%
“…Electrochromism of WO3 and MoO~ or their hydrates have been widely investigated because they have a potential as passive display electrodes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Several mechanisms of coloration have been proposed up to date: intervalence transition W 5+ --~ W 6 § (2), electron transition between donor state and conduction band or intraband transition of conduction electron (7), small polaron transition (8), and formation of F or F + centers in reduced tungsten trioxide matrices (10).…”
Section: Discussionmentioning
confidence: 99%
“…The oxidation charge density was varied in region of 0,5 to 4 C/cm2. In situ interferometric measurements shows that for oxidation charge density 1 , 1 C/cm2 the thickness of film is 240 nm, if refractive index for anodic oxide film with small content of water is n=2, 145 at X=632,8 nm [6,11]. The PAR Model 173 Potentiostat/Galvanostat was used both for oxidation of tungsten and cycling in the same > .::.…”
Section: Methodsmentioning
confidence: 99%